RANCANG BANGUN E-PESANTREN SISTEM INFORMASI SANTRI DI PONDOK PESANTREN TERPADU AL-YASINI - Teguh Pradana; Khusnul Khotimah; Saifudin . (SPIRIT, 2018)
Al-Yasini Islamic boarding school is an islamic educatioanal intitutions that famous in Est Java. Al-Yasini islamic boarding school has many kinds of institutions, there are formnal school and informal school. however, the management of data is relate with administration, students data, payment of administrations students, violations, and daily attendance of students is still done manually. Therefore made students information system based on web for help in the case record..Keyword : System Information, Website, Islamic Boarding School